Representasi Fungsi Dan Makna Ujaran Permintaan Dalam Surat Taha : Kajian Balaghah - Ridho Hidayat; Rohanda Rohanda; Palendika Alandira; Wildan Taufiq (Lingua: Jurnal Bahasa, Sastra dan Pengajarannya)
This research aims to explore the functions and meanings of kalam insya’ thalabi found in the verses of Surah Taha. The focus of the discussion is on identifying the functions, types, and meanings of insya’ thalabi, such as commands (amr), prohibitions (nahi), and questions (istifham). This study employs a qualitative research approach, utilizing a qualitative descriptive analysis method with a linguistic analysis framework.